Reduplication of nouns in Minangkabau language with Pariaman dialect in Sicincin Village, Padang Pariaman Regency - Ririn Yuliana Salevi; Muhammad Mukhlis (UIR Press, 2022)
Nouns are one of the studies in linguistics or linguistics, especially in the field of morphology. The word formation process consists of two processes, namely the morphological process and the nonmorphological process. The reason for this research is to complete the documentation of the Pariaman dialect Minangkabau language in Sicincin Village, Padang Pariaman Regency. The problem of this research is how is the form of reduplication of nouns in the Minangkabau language of the Pariaman dialect in Sicincin, Padang Pariaman Regency?. The purpose of this study is to clearly describe and document the form of reduplication of nouns in the Minangkabau language of the Pariaman dialect in Sicincin, Padang Pariaman Regency. , Record Techniques, Fishing Techniques and Record Techniques. The reduplication of nouns in terms of form and meaning of the Minangkabau language of Pariaman dialect in Sicincin Village, Padang Pariaman Regency in the form of complete or pure noun reduplication, there are 115 data, because the part of the repetition is the same as the basic word that is repeated for example: [bungo-bungo] 'bunga-bunga', [piriaɳ-piriaɳ] 'plates', [gantiaŋ-gantiaŋ] 'twigs', [tables] 'tables', [swah-paddy fields] 'rice fields', [samuik-samuik] ' ants', [kadai-kadai] 'shops', [goleh-goleh] 'glasses'. There are 4 forms of reduplication of affixed nouns, namely reduplication of nouns that have affixes in their repetition, for example: [plants] 'plants, [fruits] 'fruits', [shoots] 'pistols' ', and [drinks] 'drinks' and 1 data is a reduplication of shape-shifting nouns, for example: [sayuɣ-mayuɣ] 'vegetables'.